Digital Marketing Strategy untuk Meningkatkan Daya Saing UMKM Ayam Gepuk Pak Gendut - Rimadias, Santi; Putra, Exan Adityatama; Florencia Irena; Trismi, Jesslyn; Sendjaja, Kenji Manuel; Stephen, Yodi (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2023)
Culinary diversity in Indonesia reflects the creativity of the community in developing Micro, Small and Medium Enterprises (MSMEs). MSMEs have a significant contribution to the national economy, although they still face challenges related to the application of digital technology in marketing. This community service aims to implement a digital marketing strategy for MSMEs "Ayam Gepuk Pak Gfat". Through interviews and SWOT analysis, the Community Service Team identified problems and designed strategies in the form of social media content and digital menus. After obtaining the permit, the Community Service Team began mentoring and implementing strategies for these MSMEs. The assistance is in the form of updating content on Instagram and making digital menus. The evaluation